Pijat Oksitosin Meningkatkan Produksi ASI Pada Ibu Post Partum - Nurasih, Falya Indah; Imanah , Norif Didik Nur; Khomsah , Yuli Sya’baniah; Rantauni, Dahlia Arief (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
The problem that often occurs in post partum mothers is that breast milk has not come out, this is normal because usually from day 1 to day 7 little milk comes out so it is necessary to give an oxytocin massage. Oxytocin massage is massage along the spine down to the fifth rib bone with the aim of stimulating the hormones oxytocin and prolactin. The aim of giving oxytocin massage itself is to increase breast milk production in Mrs.S. This research method uses a case study design with a qualitative approach. The results of the research were that after being given an oxytocin massage, the volume of breast milk production increased, so that the mother was able to provide exclusive breast milk to her baby.